2022
DOI: 10.1186/s13567-022-01101-5
|View full text |Cite
|
Sign up to set email alerts
|

Molecular detection of Helicobacter spp. and Fusobacterium gastrosuis in pigs and wild boars and its association with gastric histopathological alterations

Abstract: Besides Helicobacter pylori, a Gram-negative bacterium that may cause gastric disorders in humans, non-Helicobacter pylori helicobacters (NHPH) may also colonize the stomach of humans and animals. In pigs, H. suis can induce gastritis and may play a role in gastric ulcer disease, possibly in association with Fusobacterium gastrosuis. In the present study, gastric samples from 71 slaughtered pigs and 14 hunted free range wild boars were tested for the presence of DNA of F. gastrosuis and gastric Helicobacter sp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
2

Relationship

3
2

Authors

Journals

citations
Cited by 8 publications
(16 citation statements)
references
References 41 publications
3
8
0
Order By: Relevance
“…In this study, one biopsy sample of the fundic gland zone was positive in the ureAB-based H. pylorispeci c PCR assay, while negative in the glmM-based H. pylori-speci c PCR assay, indicating that this may concern the presence of H. pylori-like organisms, which is in accordance with the results obtained by Cortez Nunes et al [11]. Further evidence concerning the existence of these potentially novel gastric Helicobacter species and their possible signi cance for gastric disease in pigs should be obtained through isolation and genomic characterization of the organisms, ideally in a large multi-farm study.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…In this study, one biopsy sample of the fundic gland zone was positive in the ureAB-based H. pylorispeci c PCR assay, while negative in the glmM-based H. pylori-speci c PCR assay, indicating that this may concern the presence of H. pylori-like organisms, which is in accordance with the results obtained by Cortez Nunes et al [11]. Further evidence concerning the existence of these potentially novel gastric Helicobacter species and their possible signi cance for gastric disease in pigs should be obtained through isolation and genomic characterization of the organisms, ideally in a large multi-farm study.…”
Section: Discussionsupporting
confidence: 92%
“…Methods used for the detection of H. pylori-like organisms were based on previous work of Cortez Nunes et al [11]. This involved a H. pylori-speci c PCR assay based on the ureAB gene [11,13], followed by a H. pylori-speci c PCR assay based on the glmM gene [11,14] which was performed in samples positive in the former PCR assay and allowed to discriminate between H. pylori and H. pylori-like organisms. Since no reports have been made of pigs naturally infected with H. pylori, the latter assay (glmM-based) was expected to be negative.…”
Section: Pcr For the Detection Of Helicobacter Pylori-like Organismsmentioning
confidence: 99%
See 1 more Smart Citation
“…Of note, Krakowka et al [24] have reported the presence of H. pylori-like organisms in pigs, which are structurally and immunologically closely related to, however antigenically distinct from, H. pylori, and morphologically distinct from H. suis, which is a well-known pathogen in pigs. Such pig associated H. pylori-like organisms have also been described by Cortez Nunes et al [25] who detected Helicobacter species in DNA samples of gastric tissue of 36 out of 71 pigs (50.7%) for which ampli cation in a ureAB gene based H. pylori-speci c PCR assay was achieved (as con rmed by sequencing), but not in a glmM gene based H. pylori-speci c PCR assay.…”
Section: Introductionsupporting
confidence: 64%
“…6, photographs of the IHC stainings of biopsies 037DA and 043DC were chosen to represent the presence of H. pylori-like organisms since these demonstrated the morphology of H. pylori most clearly. In retrospect, the H. pylorispeci c ureAB sequences obtained from these biopsies showed highest similarity to a partial coding sequence deposited in the NCBI GenBank database described as 'Helicobacter pylori isolate 39 urease subunit A and urease subunit B genes' (accession number: MW714655.1), which was obtained from a stomach sample of a wild boar and the organism was later also de ned as a H. pylori-like organism based on PCR and sequencing analysis [25].…”
Section: Discussionmentioning
confidence: 96%